Use of Emergency Department Pharmacists in Emergency Medicine Resident Milestone Assessment - Starr-Mar’ee C. Bedy; Kara B. Goddard; Julie A.W. Stilley; Christopher S. Sampson (Western Journal of Emergency Medicine, 2019)
Introduction: The use of competency-based milestones for emergency medicine (EM) was mandated by the Accreditation Council for Graduate Medical Education in 2013. However, clinical competency committees (CCC) may lack diverse, objective data to assess these new competencies. To remedy the lack of objective data when assessing the pharmacotherapy sub-competency (PC5) we introduced a unique approach that actively involves departmental clinical pharmacists in determining the milestone level achieved by the resident. Methods: Our pharmacists assess the pharmacotherapy knowledge of the residents through multiple methods: direct observation of orders, communication with the residents while performing patient care within the emergency department (ED), and real-time chart review. This observation occurs informally on a daily basis in the ED and is incorporated into the routine work of the pharmacist. The pharmacists use the PC5 sub-competency as their standard evaluation tool in this setting to keep all assessments consistent. Results: Since our residency program introduced pharmacist assessment of resident pharmacotherapy knowledge, the CCC has conducted seven biannual meetings. Of the 120 separate PC5 sub-competency assessments made during those meetings there was 100% agreement between the pharmacist’s assessment and the CCC’s final assessment of the trainee. A survey of the CCC members concluded that the pharmacists’ assessments were useful and aided in accurate resident evaluation. Conclusion: The use of ED pharmacists in assessing the pharmacotherapy sub-competency provides important information used in resident assessment of the PC5 milestone.